Foveal spatial summation in human cone mechanism - O´donell, Beatriz Maria (2011)
We measured at the fovea the chromatic contrast threshold for stimuli modulated along different chromatic directions in the isoluminant plane of MBDKL colour space, considering the two cardinal axes (L+M) and S/(L+M) and other intermediate non-cardinal directions. This psychophysical determination was conducted as a function of stimulus size. The test stimulus was a foveal isoluminant Gaussian patch with a raised cosinusoidal temporal profile superimposed on a neutral background. The task was performed binocularly. The increment threshold was measured for three observers by a Bayesian adaptive psychometric method (QUEST). The Ricco area of complete spatial summation was estimated from the threshold-versus-area curves. The perceptive fields are smaller for the L/M-cone opponent direction than the S/(L+M)-cone opponent. The perceptive field sizes for the stimuli in non-cardinal chromatic directions and stimuli modulated at the (L/M)-cone opponent direction present similar values. Measurements were made at two luminance levels, 5 and 40 cd m-2, but the differences found were small. The perceptive field sizes found could be associated with LGN area.